Parasites Infection OF Swamp Buffalo (Bubalus Bubalis) In East Sumba Regency - Saukhan, Ghiandra Naufal Syazily; Satrija, Fadjar; Murtini, Sri (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
Swamp buffalo (Bubalus bubalis) play an important role in supporting the economy and social life of the community in the East Sumba Regency. The prevalence and intensity One of the diseases still a health problem in livestock, including buffalo, is parasite infection. Research on cases of parasite infection in buffaloes in the East Sumba Regency has not been widely reported. Therefore, this study was conducted to identify the parasites that infect the buffalo as well as to measure the prevalence and infection rates. The coprological examination of 105 samples of swamp buffalo feces from the East Sumba Regency was conducted in this study. The simple flotation and the modified McMaster method were used to identify and measure the degree of infection of Nematode, Cestode, and protozoan oocyst, while the modified Danish Bilharziasis Laboratory (DBL) method was used to detect the presence of Trematodes. The results showed that 67 out of 105 buffaloes (63.81%) had parasite infections, which were caused by a single (44.76%) and mix infection (19.05%). The prevalence of infection with Nematodes, Trematodes, and Protozoan oocysts in males (73.33%) was much higher than in female (60.00%) buffalo; nevertheless, the chi-square test results showed that sex was not associated with the prevalence of parasites infection cases (p>0.05). Age was a risk factor that had a significant effect (p<0.05), with the young age group having the highest odds ratio (OR) value (5.80), followed by the age group of the calf (3.10), and pre-weaned calf (2.98). The highest to lowest infection rates were observed in Cestodes (547.03 EPG), followed by Protozoa (220.70 PG), Nematodes (84.75 EPG), and Trematodes (2.18 EPG). The present study shows that buffalo in East Sumba Regency are infected with several parasites, so control must be made to prevent losses due to the infection.Keywords - Bubalus bubalis, East Sumba, fecal examination, gastrointestinal parasites, the prevalence